Prevalence of incivility between ophthalmology and emergency medicine residents during interdepartmental consultations. Issue 4 (9th September 2021) - Mgboji, Glory E.; Woreta, Fasika A.; Fliotsos, Michael J.; Zafar, Sidra; Ssekasanvu, Joseph; Srikumaran, Divya; Zhao, Jiawei; Buccino, Daniel L.; Regan, Linda
Abstract: Objectives: Since incivility is linked to adverse effects in patient care and health care worker well‐being, evaluation of the prevalence of incivility during the formative years of residency training is warranted. The aim of this study was to determine the perceived presence and degree of incivility between emergency medicine (EM) and ophthalmology residents during emergency department (ED) consultations. Methods: We conducted a single‐site, survey‐based study, targeted to ophthalmology and EM residents. The survey we distributed included questions adapted from validated and widely used surveys measuring incivility in the workplace (Workplace Incivility Scale) and incivility within the ED. Results: Ophthalmology (13/15, 86.7%) and EM (42/48, 87.5%) residents participated, with an overall response rate of 55 of 63 (87.3%). Most residents (47/55, 85.5%) reported some degree of incivility during consultations, with a greater proportion of females reporting incivility (100%) than males (77.4%, p = 0.033). A total of 52.7% of respondents reported occurrence of incivility on a quarterly basis; 21.8% reported monthly, 10.9% weekly, and none daily. Incivilities were reported most commonly during nonurgent consults (85.5%). The two most common incivilities reported by trainees were when the other party paid little attention to their statements or opinions (80% of residents) or doubted their professional judgment (74.5% of residents). More female trainees reported jokes being told at their expense compared to males (15.8% vs. 0%, p = 0.049). Residents most often attributed incivility to stress (78.2%), loss of empathy/burnout (63.6%), or attempts to shift responsibility to another party (60.0%). Among EM residents surveyed, incivility was identified as occurring most often during consultations with surgical specialties. Conclusions: Incivility during interdepartmental consultations between EM and ophthalmology is commonly reported by physicians‐in‐training. It occurs more often during consultations deemed as nonurgent and is more commonly reported by females. Given its associations with adverse outcomes, interventions to decrease incivility early in training may be warranted.